The Sun and the Shadow in a Bullring: Faces of the Street in the Plaza de Acho. Reflections on a Peruvian Book of Profile Features and a Photo-Essay - Luis Cáceres Álvarez (Ибероамериканские тетради)
The COVID-19 pandemic, which officially began in the Peruvian capital on March 6, 2020, revealed an alarming situation: more than 3,000 people were living on the streets. Because of the emergency, the historical Plaza de Acho, one of the oldest bullrings in America and the world, became a temporary refuge for homeless people in the first months of the pandemic. In Home for Everyone four journalists documented stories of people who found themselves living in this emblematic place. The book, which combines profile features and a photo-essay, explores the correlation between the narration and presentation of these stories. Not only is this work informative, but it also prompts readers to reflect on the human condition, social structure, and collective memory in times of crisis. This is a chronicle of a difficult period, which also shows tensions and contradictions in an unequal society. By delving into the vicissitudes of the lives of its protagonists, it offers a sensitive yet profound outlook that defies indifference and reminds us of the value of human dignity in the face of adversity. In addition, this book is a transmitter of Peruvian culture, as it displays the language and culture of Lima’s streets and allows us to meet the little-known characters of its cultural landscape.